(3cJGH GdBdg GdTGedI aj Gdadcs - (3CHh eMehO Hf NVQ GdNLfOj,J (B390 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg aEf deG hLOJ GdYde hEf cGf eTQakG aEfg jROGO GdTQa s
(3BNQgG (B:s
(3hjfXQ ce JMQc GdhQi Ch GdehQjfi LejYkG Ydi eG LQJ Ydjg GdYGOg aeG GLJeY efg GdYGOGJ LejYkG , Ch YOO hGMO hPdc CffGf s
(3ajgG YOO ef GdQShes
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B390 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B970) s
Keywords: (3Gdadcs